The factor influence people to invest in unit trust: CWA CIMB principal brand / Ummi Khumairaq Saifuzzaman - Saifuzzaman, Ummi Khumairaq (2019)
This research was focus on the interest of people which is focus to the influencing factors for them to invest in unit trust which is Cimb Wealth Advisor (CWA) Cimb-principal brand. As well as studying the relationship between the independent and dependent variables for this paper. The result of data analysis can be concluded that there are four main factor that have strong relationship in influencing the interest of investors to invest in CWA unit trust which is the factor of past performance, risk tolerance, size of funds and shariah based funds. In the other hand, the past performance factor is the most affected in order to influence investor to invest in CWA unit trust. To better understand the personal perception that influences the selection of CWA unit trust, the unit trust management companies need to hire professional unit trust sales personnel and consultants who understand personal investment philosophy to market them to the right investors.